(untitled) (Research, Society and Development, 2020)
The objective of the work is to describe the results of a health promotion activity developed by second-year medical students at the Federal University of Pará, which took place in a municipal school in the public school system, located in the municipality of Belém in the state of Pará. The purpose of the project was to promote an educational action on the primacy of maintaining hygiene habits in achieving well-being. This action was directed by the axis of Comprehensive Health Care in partnership established with the Family Health Strategy of the region, where we sought to promote actions to promote the development of this community. The activity was carried out with students from the 5th year of elementary school. The students were divided into 4 groups and each was under the responsibility of a health station with a theme related to the chosen hygiene. Through the application of active methodologies, the work carried out at the school made students aware of the proper habits of oral hygiene, hands, hair and the environment. It was concluded that there is a need to carry out a systematic and continuous work through an open channel between community / school / environment so that students grow, understanding the importance of implementing an interconnected and present practice of health education in the different areas of their activities.